Examining Drone Logistics Solutions in Retail - Füzesi, István; Preznyák, Szabolcs; Szilágyi, Róbert; Lengyel, Péter (International Journal of Engineering and Management Sciences, 2018)
The possibilities of using drones in transportation will be determined by the capabilities of drone technology, legislation, various advocacy and trade unions, and the degree of general acceptance. Technology and infrastructure are given, customer habits and needs are favourable, and emissions generated by packets moving between two points are growing steadily. Despite these favourable conditions, the effects of drone use should be thoroughly reviewed. The environmental impacts of the project were analyzed by PEST analysis and the main influencing factors were studied using the Porter model. Concluding our results based on questionnaire surveys and feasibility examinations of fast food delivery, it can be said that a system based on drones can efficiently be operated and cost-effective using round trips, however, the legal issues and uncertainties that arise in the delivery of drone hippers remain a very significant hindering factor for a long time.